2021
DOI: 10.1093/biolre/ioab193
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic profiling of neonatal mouse granulosa cells reveals new insights into primordial follicle activation

Abstract: The dormant population of ovarian primordial follicles is determined at birth and serves as the reservoir for future female fertility. Yet our understanding of the molecular, biochemical, and cellular processes underpinning primordial follicle activation remains limited. The survival of primordial follicles relies on the correct complement and morphology of granulosa cells, which provide signalling factors essential for oocyte and follicular survival. To investigate the contribution of granulosa cells in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…Analysis of PadI6 , Zp1 , Zp2 and Nlrp14 expression via a RT-qPCR in F1–D1 and F1–D2 oocytes confirmed these results ( Figure 10 F). The expression of several genes involved in primordial follicle activation [ 80 ] was modified in F1–D1 ovaries, such as Nlrp4f and Nlrp14 , that are downstream of Figla and Sohlh2 , respectively, in the promotion of secondary follicle oocyte growth [ 81 , 82 ]. Tcf21 ( Pod1 ) was upregulated in D2 ovaries.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of PadI6 , Zp1 , Zp2 and Nlrp14 expression via a RT-qPCR in F1–D1 and F1–D2 oocytes confirmed these results ( Figure 10 F). The expression of several genes involved in primordial follicle activation [ 80 ] was modified in F1–D1 ovaries, such as Nlrp4f and Nlrp14 , that are downstream of Figla and Sohlh2 , respectively, in the promotion of secondary follicle oocyte growth [ 81 , 82 ]. Tcf21 ( Pod1 ) was upregulated in D2 ovaries.…”
Section: Resultsmentioning
confidence: 99%
“…Historically, samples isolated using animal-age- or oocyte size-specific methods have been applied to the studies of ovarian follicle and oocyte development, for example, using different perinatal timepoints for collecting primordial or primary stage cells ( Pan et al 2005 , Ford et al 2021 ) or collecting size-specific oocytes to represent other follicular stages ( Veselovska et al 2015 , Lv et al 2021 ). These approaches allow for efficient sample collection and analysis in bulk quantity and have therefore established fundamental cellular events as well as identified critical players that drive follicle development.…”
Section: Discussionmentioning
confidence: 99%
“…Several of these targets have been characterized in follicle activation. For example, studies have identified the importance of WNT signaling in pre-granulosa to granulosa cell differentiation ( Ford et al 2021 , Habara et al 2021 ). Further, TGFB1 signaling mediates cell cycle arrest in pre-granulosa cells ( Hardy et al 2018 , Granados-Aparici et al 2019 ), and inhibiting TGFB1 signaling promotes follicle activation ( Wang et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect is likely through its interaction with the mTORC1-KITL signaling pathway in pregranulosa cells and the KIT-PI3K signaling in oocytes ( 290 , 292 ). Recent studies suggest an involvement of WNT signaling during granulosa cell differentiation from squamous to cuboidal and PFA ( 293 , 294 ). Mouse studies have also suggested that the TNFα signaling through the receptor TNFR2 and downstream nuclear factor κ-light-chain-enhancer of activated B cells (NF-κB) pathway would be key positive regulators of PFA.…”
Section: Primordial Follicle Recruitment Into the Growing Poolmentioning
confidence: 99%